ANALISIS SEMIOTIKA ROLAND BARTHER PADA FILM SEX EDUCATION - Tiara Hanandita; Linggar Nur Imani; Sinta Dwi Rahayu; Refti Handini (Kafa`ah: Journal of Gender Studies, 2022)
This study aims to describe the forms of denotative meaning, connotative meaning, and myths contained in the film “Sex Education Season 1”.This research uses descriptive qualitative and leads to the use of semiotic analysis from Roland Barthes. The results obtained from the research on the film “Sex Education Season 1” include: 1) the meaning of denotation and the meaning of connotation in this film which provides an understanding of the importance of sexuality education for adolescents; 2) the myth that can be concluded in this study is that adolescents still do not get the facts from their sexuality acts, so it is related to decision making in terms of sex.